LOSSES IN THE PEANUT MECHANICAL DIGGING AS A FUNCTION OF THE DIGGER SHAKER ROTATION - Bertonha, Rafael Scabello; Silva, Rouverson Pereira; Furlani, Carlos Eduardo Angeli; Cavichioli, Fabio Alexandre (REVISTA DE AGRICULTURA, 2014)
Due to the many factors that affect the peanut crop, especially the care in the digging and equipment configuration are very important as it may affect significantly the losses in this crop. The aim of this work was to evaluate the losses in peanut digging as a function of different rotations of the digger shaker inverter. The experiment was conducted at Teaching, Research and Extension Farm at UNESP - SÃ£o Paulo State University, Jaboticabal city, SP, Brazil. Was used seeds of peanut (IAC Runner 886 cultivar) and for the peanut digging was used a digger 2x1 (two rows per one windrow), pulled by a tractor with a power of 80.9 kW. The experimental design was a randomized blocks with five replications. Was used the tractor engine rotations at 20.0, 23.3, 26.7 and 30.8 Hz, which resulted in rotations in the shaker conveyer of 1.7, 1.8, 2.1 and 2.4 Hz. For the statistical analysis, was determined the descriptive analysis to permit a visualization of the general behavior of the data, determining measures of central tendency (arithmetic mean and median), dispersion (standard deviation and coefficient of variation), skewness and kurtosis. Was conducted to the Anderson-Darling test to verify the normality of the data, and when necessary, was proceeded to the standardization by the transformation. The visible, invisible and total losses were higher with the increasing of the digger shaker rotation.